Hubungan pengetahuan dan konsumsi vitamin c dengan kadar timbal dalam urin remaja di kecamatan Curug - Salsabilla, Nilna Fasyya; Hananingtyas, Izza (Institute for Advanced Science, Social, and Sustainable Future, 2023)
Lead is a toxic and pervasive metal. Chronic exposure to low levels is responsible for significant health effects, particularly in early adolescent. Prevention remains the best option for reducing lead exposure. The objective of the present study was to determine the association between knowledge and consumption of vitamin c with lead exposure in early adolescents’ urine. This research is a quantitative study with cross sectional study design. Research subjects were 52 adolescents aged 12-16 years from Kadu Village, Curug. We examined associations of levels of knowledge and consumption of vitamin c with urine lead levels (Pb-U). We used a brief questionnaire on prevention for lead poisoning, included to measure knowledge (from Chicago Lead Knowledge Test Questionnaire) and daily intake of vitamin C (from Food Frequency Questionnaire) completed by respondents. Pb-U was measured using ICP-OES. The average urine lead levels of the early adolescents was 28,88 μg/L (median: 27,70 μg/L; CI 95% 24,85-32,90) (n=52), and Std. 14,46 μg/L. There was a significant difference between knowledge and the levels of Pb in the urine of early adolescent (p = 0,045). There was no significant difference between the consumption of vitamin c and the levels of Pb in the urine of early adolescent (p = 0,379). The hypothesis proved that the levels of knowledge affects lead levels in the urine of early adolescents. Therefore, it is suggested that government should educate the public about lead and its preventive actions and collaborate with policy makers to be more efficient.